Effect of NPK fertilizers on growth, oil yield and quality of French basil (Ocimum basilicum L.) - D Patra, K Singh, P P Singh, S U Beg, D Kumar, D (Journal of Spices and Aromatic Crops, 2004)
A field trial was conducted at Lucknow (Uttar Pradesh), to study the effect of different levels of NPK on growth, oil yield and quality of methyl chavicol rich cultivar of French basil (Ocimum basilicum). Five levels of N, P,05 and K,O namely, control (no fertilizer), 37.5, 20.0 and 20.0 kg ha-1, 56.25, 30.00 and 30.00 kg ha-1, 75.0, 40.0 and 40.0 kg ha-1 and 93.5, 50.0 and 50.0 kg ha-1 were evaluated. The results indicated that application of N, P,05 and K,O @ 75.0, 40.0 and 40.0 kg ha-1 increased plant height, fresh herbage, dry matter and oil yield significantly over control. The oil content in fresh herbage and its quality were not influenced by fertilizer application.